2018
DOI: 10.1039/c8ta03521k
|View full text |Cite
|
Sign up to set email alerts
|

Realization of n-type and enhanced thermoelectric performance of p-type BiCuSeO by controlled iron incorporation

Abstract: Fe-doping enables n-type BiCuSeO and improves the performances of p-type BiCuSeO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…It is normally reported that BiCuSeO samples exhibit higher TE performance along the direction perpendicular to the pressing direction . In this work, we had measured part of sample ( x = y = 0.08) along two directions, the result further confirmed the better performance along this directions (Figure ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It is normally reported that BiCuSeO samples exhibit higher TE performance along the direction perpendicular to the pressing direction . In this work, we had measured part of sample ( x = y = 0.08) along two directions, the result further confirmed the better performance along this directions (Figure ).…”
Section: Resultssupporting
confidence: 73%
“…It is normally reported that BiCuSeO samples exhibit higher TE performance along the direction perpendicular to the pressing direction. 32,33 In this work, we had measured part of sample (x = y = 0.08) along two directions, the result further confirmed the better performance along this directions ( Figure S3). Hence, we measured the thermoelectric properties along the direction perpendicular to the pressing direction for all samples, and inset figure of Figure 3B shows the schematic diagram of measurement direction.…”
Section: Methodssupporting
confidence: 64%
“…BiCuSeO is an intrinsic p -type semiconductor due to Bi and Cu vacancies. Recently, Pan et al realized n -type BiCuSeO by iron incorporation [ 117 ] and Zhang et al [ 118 ] presented the realization of n -type BiCuSeO by filling these vacancies with additional Bi and Cu and simultaneously introducing Br and I at the Se site for electron doping; the above resulted with Seebeck coefficients of up to −550 V K −1 .…”
Section: Oxides and Oxyselenidesmentioning
confidence: 99%
“…Best performing oxide‐based materials highlighting (A) highest σ, (B) low κ t and (C) ZT value via miscellaneous optimization techniques …”
Section: High Performance Inorganic Te Materialsmentioning
confidence: 99%